Protective Role of Vitamin E on Methotrexate Induced Renal Injury in Rabbits: - Taghizadieh, Mohammad; Afshari, Fatemeh; Shokri, Nazila; Hajipour, Babak (Galen Medical Journal, 2014)
Background and Aims: Methotrexate (MTX), a folic acid antagonist, is widely used as a treatment for malignancies as well as in the treatment of various inflammatory and autoimmune disorders. Nephrotoxicity is an important side-effect of this drug. Prevention and treatment of MTX-induced renal dysfunction are essential to prevent potentially life-threatening MTX-associated toxicities, Present study was undertaken to determine whether vitamin E could ameliorate methotrexate-induced oxidative renal injury in rabbit. Materials and methods: Twenty eight rabbits were randomly assigned into four groups (n=7): Group 1 (control group), Group 2 (Received 20mg/kg MTX): Group 3 (Received MTX plus vitamin E 100 mg/kg orally), group 4: (vitamin E 100 mg/kg orally). On 6th day rabbits were anesthetized and renal tissue sampled for pathologic and biochemical assessment. Results: Data showed that renal tissue injury index and malondialdehyde (MDA)level were lower in MTX+vitamin E group comparing to MTX group significantly (P<0.05). Renal tissue injury index and MDA were higher in MTX+vitamin E group comparing to control group significantly (P<0.05). Conclusion: These findings suggest that vitamin E, by improving cellular anti-oxidant defense system, reduction in lipid peroxidation production and tissue damage, appears to have a protective role in the MTX-induced oxidative injury in renal tissue, however, further studies are essential to elucidate the exact mechanisms of MTX-induced renal toxicity, and protective effect of vitamin E.